Tingkat Akurasi dan Presisi Data Hujan Sensor Peralatan Otomatis terhadap Penakar Hujan Konvensional di Provinsi Sulawesi Tengah (Buletin GAW Bariri (BGB), 2023)
Rainfall is the height of rainwater that falls on a flat place assuming it does not evaporate, does not seep and does not flow. Rainfall can be measured using conventional and automatic equipment. The equipment for measuring rainfall is an observatory measurer (Ombrometer), while conventional equipment uses bucket typing sensors from the Automatic Rain Gauge (ARG), Automatic Weather Station (AWS) and Automatic Agroclimate Weather Station (AAWS). Rain measured using conventional and automatic equipment has the same units, namely millimeters (mm). Analysis was carried out to determine the quality of monthly rainfall data from automatic equipment on rain posts using Taylor diagrams. The Taylor diagram summarizes three frequently used indicators including correlation, standard deviation, and centered root mean square error. The results show that ARG Palolo, AWS Dolago and AAWS Sidondo are the best among each of the 3 types of automatic equipment, consisting of 12 ARG Palolo, 3 AWS and 3 AAWS in Central Sulawesi Province. ARG Palolo has a level of accuracy and precision that is closest to the rain post, namely having a correlation value of 0.79, p – value 0.00029, centered RMS Error of 95 and standard deviation of 97.15. AWS Dolago has a level of accuracy and precision that is closest to the rain post, namely having a correlation value of 0.975, p – value 1.42E – 10, centered RMS Error of 22.4 and standard deviation of 107.788. AAWS Sidondo has a level of accuracy and precision that is closest to the rain post, namely having a correlation value of 0.455, p – value 0.0768, centered RMS Error of 61.3 and standard deviation of 197.55.